The overlooked but crucial role of rare algal species in ecosystem stability and diversity: Examples from freshwater lakes East of the Hu Huanyong line - Wei Wang; Zhongshi He; Xinyue Yang; Junping Lv; Xudong Liu; Shulian Xie; Jia Feng (Ecological Indicators)
Most biotic and abiotic interactions among aquatic species in freshwater ecosystems remain unknown, which frequently results in the assumption that dominant species play the most crucial ecological role. This tendency is particularly evident in studies of phytoplankton communities that has predominantly focused on common and abundant members such as cyanobacteria, which overlooks the ecological contributions of rare (non-dominant and uncommon) species. This study investigated freshwater ecosystems east of the Hu Huanyong Line, examining the ecological roles of common and rare algal genera. Results indicated that common algal genera significantly influence community dynamics and occupy central positions in ecological networks. By contrast, rare algal genera, situated at network peripheries, were crucial for ecosystem stability and maintaining ecosystem stability through distinct “presence or absence patterns”. Furthermore, the diversity and abundance of rare algae were negatively correlated with multiple nutrient factors (−0.347, −0.327), contrasting the positive relationship observed for common algae (0.378, 0.292), which indicates their vulnerability to eutrophication. Overall, this study emphasizes the importance of conserving rare algal species in order to maintain ecosystem stability and biodiversity in the face of global environmental change.